Mantle-to-crust metal transfer by nanomelts - Erwin Schettino; José María González-Jiménez; Claudio Marchesi; Francesco Palozza; Idael F. Blanco-Quintero; Fernando Gervilla; Roberto Braga; Carlos J. Garrido; Marco Fiorentini (Communications Earth & Environment, 2023)
Abstract The transfer of chalcophile metals across the continental lithosphere has been traditionally modeled based on their chemical equilibrium partitioning in sulfide liquids and silicate magmas. Here, we report a suite of Ni-Fe-Cu sulfide droplets across a trans-lithospheric magmatic network linking the subcontinental lithospheric mantle to the overlying continental crust. Petrographic characteristics and numerical calculations both support that the sulfide droplets were mechanically scavenged from the mantle source during partial melting and transported upwards by alkaline magmas rising through the continental lithosphere. Nanoscale investigation by high-resolution transmission electron microscopy (HR-TEM) documents the presence of galena (PbS) nanoinclusions within the sulfide droplets that are involved in the mantle-to-crust magma route. The galena nanoinclusions show a range of microstructural features that are inconsistent with a derivation of PbS by exsolution from the solid products of the Ni-Fe-Cu sulfide liquid. It is argued that galena nanoinclusions crystallized from a precursor Pb(-Cu)-rich nanomelt, which was originally immiscible within the sulfide liquid even at Pb concentrations largely below those required for attaining galena saturation. We suggest that evidence of immiscibility between metal-rich nanomelts and sulfide liquids during magma transport would disrupt the classical way by which metal flux and ore genesis are interpreted, hinting for mechanical transfer of nanophases as a key mechanism for sourcing the amounts of mantle-derived metals that can be concentrated in the crust.